EFFECT OF Ni DOPING AND SYNTHESIS TEMPERATURE ON THE PROPERTIES OF NIR-REFLECTIVE ZnFe₂O₄ BLACK PIGMENTS - Mantana Suwan; Nuchjarin Sangwong; Supothina Sitthisuntorn (Ceramics-Silikáty, 2020)

(untitled)
NIR-reflective Ni-doped ZnFe₂O₄ black pigments with the general formula of Zn(1-x)NixFe₂O₄ have been synthesized by a conventional solid-state reaction of ZnO, Fe₂O₃ and NiO. The effect of Ni doping was studied by adding various amounts of NiO, with x ranging from 0 to 1. Proportional amounts of ZnO, Fe₂O₃ and NiO were homogeneously mixed together by means of wet milling, followed by filtration and drying. Then, the mixtures were calcined at 1000 and 1100 °C for 3 h. XRD analysis of the undoped pigments revealed the presence of pure ZnFe₂O₄ in all synthesis conditions. The addition of NiO dopant into the ZnFe₂O₄ caused a gradual shift of the diffraction peaks toward higher angles due to the substitution of Zn2+ by the smaller Ni2+ to form the Zn(1-x)NixFe₂O₄. Upon the increase of NiO doping content and calcination temperature, the color hue of the pigments changed from light brown to brownish black, and a gradual reduction of the NIR reflectance was observed. For the black pigments which were synthesized at 1100 °C, the band-gap energy changed from 2.05 eV for ZnFe₂O₄ (x=0) to 1.65 eV for NiFe₂O₄ (x=1). At the optimum synthesis condition, resulting in black color hue and high NIR reflectance, the Zn0.5Ni0.5Fe₂O₄ pigment synthesized at 1100 °C had high NIR reflectance of 55.3%.